A92 ANALYTICAL PERFORMANCE OF A SMARTPHONE-BASED PATIENT MONITORING SYSTEM COMPARED TO ELISA FOR THE MEASUREMENT OF FECAL CALPROTECTIN IN IBD PATIENTS - Farrag, K (J Can Assoc Gastroenterol, 2019)
BACKGROUND: Inflammatory bowel disease (IBD) is a chronic intestinal inflammatory disorder presenting with phases of active inflammation, remission and relapse. Fecal calprotectin (fcal) measurement has become established for the monitoring of inflammation activity. Periodical assessment of fcal levels has been demonstrated to be an important non-invasive indicator of treatment efficacy and predictor of relapse. However, until now, fcal determination required patients to send stool samples in for laboratory analysis, resulting in a long delay between sample collection and final test results. We developed a simple home-based calprotectin test system to allow patients to regularly monitor their own inflammatory status by testing fcal levels in the comfort of their own home. QuantOnCal consists of a stool extraction device (IDK® Extract) and an immunochromatographic rapid test performed by a smartphone App via the phone camera. Results are automatically sent to a webserver, where they are displayed for monitoring by the consulting physician or IBD nurse. AIMS: The objective of this study was to validate the QuantOnCal test system by comparing its quantitative performance with a standard ELISA-based method. METHODS: Stool samples from 157 IBD and non-IBD patients containing various levels of calprotectin (95 IBD: UC/CD/active/remission, 42/43/48/47; 33 IBS: 23 Chm: 6 Div) were either loaded onto immunochromatographic test cassettes (TCs) or analysed with a commercial ELISA test (Immundiagnostik, Bensheim, Germany). The QuantOnCal app was installed on different smartphones including iPhone, Samsung, LG and Motorola models. Agreement between QuantOnCal testing versus ELISA was assessed by Analyse-it for Microsoft Excel. RESULTS: The QuantOnCal system produces a quantitative test result between 25–2000 mg/g fcal/g of stool, covering the clinically relevant range of this biomarker. The total agreement (TA) was 94.6% with 0% false positive and 0% false negative rates. The TA for fcal between the different smartphone models was 91.3%. CONCLUSIONS: QuantOnCal is a new, complete and validated test system which allows the IBD patient to monitor and follow his inflammatory status by measuring the IBD biomarker, faecal calprotectin, using his/her own smartphone. The performance of the QuantOnCal test system was shown to be comparable to the professional, ELISA-based method. Abbreviations IBD, inflammatory bowel disease; Chm, Carbohydrate malabsorption; UC, ulcerative colitis; CD, Crohn’s disease; Div, Diverticulitis; IBS, irritable bowel syndrome; TA, total agreement FUNDING AGENCIES: Immundiagnostik AG, Bensheim, Germany.